Manufacturing processes for design professionals - Thompson, Rob (Thames & Hudson Ltd, 2007)
Today's product designers are presented with a myriad of choices when creating their work and preparing it for manufacture. They have to be knowledgeable about a vast repertoire of processes, ranging from what used to be known as traditional "crafts" to the latest technology, to enable their designs to be manufactured effectively and efficiently. Information on the internet about such processes is often unreliable, and search engines do not usefully organize material for designers. This fundamental new resource explores innovative production techniques and materials that are having an impact on the design industry worldwide. Organized into four easily referenced parts - Forming, Cutting, Joining, and Finishing - over seventy manufacturing processes are explained in depth with full technical descriptions; analyses of the typical applications, design opportunities, and considerations each process offers; and information on cost, speed, and environmental impact. The accompanying step-by-step case studies look at a product or component being manufactured at a leading international supplier. A directory of more than fifty materials includes a detailed technical profile, images of typical applications and finishes, and an overview of each material's design characteristics. With some 1,200 color photographs and technical illustrations, specially commissioned for this book, this is the definitive reference for product designers, 3D designers, engineers, and architects who need a convenient, highly accessible, and practical reference.